EDUKASI PENCEGAHAN PENULARAN COVID-19 KELURAHAN PASIR PANJANG KECAMATAN KOTA LAMA KOTA KUPANG - Yulsy Marselina Nitte; Agnes M.D Rafael; Delila Malafu; Maria H Roar (Pengabdian Masyarakat Ilmu Pendidikan, 2021)
Coronavirus Disease 2019 (Covid-19) is a disease that began with the emergence of cases of pneumonia of unknown etiology in Wuhan, China at the end of December 2019. However, it has spread in Indonesia, including in Kupang city. In Kupang city, the number of positive confirmed cases has reached 5934 people. Seeing the high number of cases, the PKM team felt the need to carry out educational PKM activities to prevent the transmission of COVID-19 through socialization, distribution of masks, and hand sanitizers with the aim of providing education or socialization regarding the symptoms caused, how to spread and transmit the virus, how to treat the disease. as well as preventive Keywords: education, prevention, covid 19